Journal of emerging market finance. - Industrial Credit and Investment Corporation of India ([New Delhi] Sage, 2002)
The Journal of Emerging Market Finance is a forum for debate and discussion on the theory and practice of finance in emerging markets. While the emphasis is on articles that are of practical significance, the journal also covers theoretical and conceptual aspects relating to emerging financial markets.
UP System perpetual contents: 2019
Keywords: Banks and banking -- Developing countries -- Periodicals; Financial institutions -- Developing countries -- Periodicals; Securities -- Developing countries -- Periodicals; finance; financial management; money market; Financial Management, Accountancy